Functional coordination of non‐myocytes plays a key role in adult zebrafish heart regeneration. (15th September 2021) - Ma, Hong; Liu, Ziqing; Yang, Yuchen; Feng, Dong; Dong, Yanhan; Garbutt, Tiffany A; Hu, Zhiyuan; Wang, Li; Luan, Changfei; Cooper, Cynthia D; Li, Yun; Welch, Joshua D; et al.
Abstract: Cardiac regeneration occurs primarily through proliferation of existing cardiomyocytes, but also involves complex interactions between distinct cardiac cell types including non‐cardiomyocytes (non‐CMs). However, the subpopulations, distinguishing molecular features, cellular functions, and intercellular interactions of non‐CMs in heart regeneration remain largely unexplored. Using the LIGER algorithm, we assemble an atlas of cell states from 61, 977 individual non‐CM scRNA‐seq profiles isolated at multiple time points during regeneration. This analysis reveals extensive non‐CM cell diversity, including multiple macrophage (MC), fibroblast (FB), and endothelial cell (EC) subpopulations with unique spatiotemporal distributions, and suggests an important role for MC in inducing the activated FB and EC subpopulations. Indeed, pharmacological perturbation of MC function compromises the induction of the unique FB and EC subpopulations. Furthermore, we developed computational algorithm Topologizer to map the topological relationships and dynamic transitions between functional states. We uncover dynamic transitions between MC functional states and identify factors involved in mRNA processing and transcriptional regulation associated with the transition. Together, our single‐cell transcriptomic analysis of non‐CMs during cardiac regeneration provides a blueprint for interrogating the molecular and cellular basis of this process. Synopsis: Using single cell technology, this study delineates the cellular and transcriptomic dynamics of major non‐myocyte populations during cardiac regeneration and demonstrates a critical role of functional coordination of non‐myocytes in adult zebrafish heart regeneration. Multiple novel subpopulations for major non‐myocyte cell types are identified that exhibit distinct tempo‐spatial dynamics during cardiac regeneration. Highly cooperative interactions of non‐myocyte subtypes through cell‐cell signaling are observed. The data indicate an important role for macrophages in inducing the activated fibroblast and endocardial endothelial cell subpopulations. Development of the new computational algorithm Topologizer reveals the topological relationship of the cellular manifolds. Dynamic transitions between macrophage functional states and factors involved in mRNA processing and transcriptional regulation associated with the transition are uncovered. Abstract : Using single cell technology, this study delineates the cellular and transcriptomic dynamics of major non‐cardiomyocyte populations during adult zebrafish heart regeneration.